The Correlation between Students’ Reading Habit and Their Reading Comprehension Achievement - Resta, Irmanda Ayu; Amalia, Shynta; Amrina, Rizqy Dwi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study has objectives to discover the significant correlation and influence between reading habits and their reading comprehension successes of students. This study took a quantitative approach, implementing a correlational research method. The research population came from a total of 416 eleventh grade students at SMAN 21 Palembang. The cluster random selection technique was used to choose three classes of 104 students each. The data were gathered through the use of a questionnaire designed to assess reading habits, as well as a test aimed at assessing reading comprehension achievement. The results demonstrated that there was an important relationship between students' reading habits and their reading comprehension achievement, with the r obtained (.321) was being greater than the r-table (.192) and the significant value achieved .001, which was less than .05. Furthermore, the regression analysis result displayed that reading habit significantly contributed to reading comprehension achievement, with the R-square value .118, which stating that students' reading habit contribute 11.8% to their reading comprehension achievement.